2023
DOI: 10.1021/acsomega.3c02699
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Alginate-Based Nanogels as Sustained Drug Carriers for Caffeine

Abstract: The objective of this study is to design a polymeric network of nanogels for sustained release of caffeine. Therefore, alginate-based nanogels were fabricated by a free-radical polymerization technique for the sustained delivery of caffeine. Polymer alginate was crosslinked with monomer 2-acrylamido-2-methylpropanesulfonic acid by crosslinker N′,N′-methylene bisacrylamide. The prepared nanogels were subjected to sol–gel fraction, polymer volume fraction, swelling, drug loading, and drug release studies. A high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 80 publications
1
3
0
Order By: Relevance
“…This augmentation in negative charge results in heightened repulsion between the nanogels and DOX, consequently leading to increased drug release. These results align with those of Suhail et al, who observed similar trends of enhanced drug release from alginate- g -poly(2-acrylamido-2-methylpropanesulfonic acid) nanogels at pH 7.4 compared to 4.6 …”
Section: Resultssupporting
confidence: 92%
“…This augmentation in negative charge results in heightened repulsion between the nanogels and DOX, consequently leading to increased drug release. These results align with those of Suhail et al, who observed similar trends of enhanced drug release from alginate- g -poly(2-acrylamido-2-methylpropanesulfonic acid) nanogels at pH 7.4 compared to 4.6 …”
Section: Resultssupporting
confidence: 92%
“…The 5-FU content of nanogels was estimated in deionized water using the extraction method [ 61 ]. The desired amount of 5-FU-loaded dry nanoparticles was extracted in 100 mL of deionized water at room temperature under stirring until all the drug was removed from the nanogels.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, Suhail et al 71 have created a network of nanogels using polymers to achieve a continuous release of caffeine. To attain this, they employed a free-radical polymerization method to fabricate alginate-based nanogels.…”
Section: Polysaccharide-based Nanogels For Drug Deliverymentioning
confidence: 99%